Technical Application Motivational Interviewing in Overcoming Regret in Adolescents Who Become a Drug Courier - Yestapiani, Melda; Suryati, Suryati; Fitri, Hartika Utami; Hernisawati, Hernisawati; Junaidi, Junaidi (Scidacplus, 2023)
This research is entitled the application of motivational interviewing techniques in overcoming regret in adolescents who become drug couriers in Kandis Village. A Regret is an act that acknowledges all the mistakes that have been made and is serious about not repeating these actions. This study aims to determine the factors that cause adolescents to become drug couriers and to find out the description of the regret experienced by the client in Kandis Village. To find out how motivational interviewing techniques are applied to overcome regret for clients